Cross-diffusion Effects on MHD Mixed Convection over a Stretching Surface in a Porous Medium with Chemical Reaction and Convective Condition - BHUVANESWARI, Marimuthu; ESWARAMOORTHI, Sheniyappan; SIVASANKARAN, Sivasankaran; HUSSEIN, Ahmed Kadhim (Engineering Transactions, 2019)
In this paper, we investigate the Dufour and Soret effects on MHD mixed convection of a chemically reacting fluid over a stretching surface in a porous medium with convective boundary condition. The similarity transformation is used to reduce the governing non-linear partial differential equations into an ordinary differential equations. Then, they are solved analytically by using homotopy analysis method (HAM) and are solved numerically by Runge-Kutta fourth order method. The analytical and numerical results for the velocity, temperature, concentration, skin friction, Nusselt number and Sherwood number are discussed.